A process for the manufacture of high-temperature bi-epitaxial Josephson junctions - De Villiers, Hendrik Adrianus Cornelis (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.